PROFIL FUNGSI KOGNITIF PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Noor Alia Susianti,* Astuti,** Ahmad Asmedi,** Abdul Gofir,** Bambang Djarwoto*** (NEURONA, 2015)
INTRODUCTION COGNITIVE FUNCTION IMPAIRMENT IS FREQUENTLY PRESENT IN CHRONIC KIDNEY DISEASE CKD PATIENTS WHO ARE UNDERGOING HEMODIALYSIS CURRENT RESEARCH ON COGNITIVE IMPAIRMENT AMONG HEMODIALYSIS PATIENTS SHOWSVARYING RESULTS